2018
DOI: 10.1007/398_2018_11
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Chemistry, Pesticide Use, and Environmental Fate of Sulfur Dioxide, as Used in California

Abstract: Sulfur dioxide (SO) is an atmospheric pollutant that is moderately persistent in the atmosphere and highly water soluble. When applied as a pesticide, SO may be transported, deposited, or transformed in various chemical reactions. SO participates in the sulfur biogeochemical cycle, which involves complex reactions of sulfur-containing compounds between abiotic and biotic components of ecosystems. The main degradation route of SO is atmospheric oxidation, and sulfur oxides may undergo long-distance transport pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…48 49 Originating from numerous industrial processes, SO 2 has been confirmed to affect human health by irritating the respiratory tract, promoting oxidative damage and decreasing immunity. [50][51][52][53] However, Wei et al showed that SO 2 exposure was associated with an increased risk of HFMD in Hefei, 46 and Yan et al found no relationship between SO 2 exposure and HFMD in Shenzhen. 16 Additional evidence is needed to confirm the association between SO 2 and HFMD.…”
Section: Discussionmentioning
confidence: 99%
“…48 49 Originating from numerous industrial processes, SO 2 has been confirmed to affect human health by irritating the respiratory tract, promoting oxidative damage and decreasing immunity. [50][51][52][53] However, Wei et al showed that SO 2 exposure was associated with an increased risk of HFMD in Hefei, 46 and Yan et al found no relationship between SO 2 exposure and HFMD in Shenzhen. 16 Additional evidence is needed to confirm the association between SO 2 and HFMD.…”
Section: Discussionmentioning
confidence: 99%
“…Organophosphorus poisoning is a public health issue, with 3,000,000 instances of poisoning and 220,000 deaths reported each year around the world, with the vast majority of cases occurring in developing countries (Craig 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although remarkably successful, extensive pesticide usage gave birth to new problems, the most important one of which were environmental toxicity, and bioaccumulation [21][22][23][24][25]. Extensive and random usage, e.g., inadequate application and spraying equipment and poor storage techniques resulted in soil, water, and food contamination that threatened public health and non-target organisms [26][27][28][29][30]. Groundwater contamination by the leaching of agricultural pesticides from soils is a serious problem leading to pollution of the aquatic environment [24,31,32].…”
Section: Accepted Articlementioning
confidence: 99%
“…Increased reactive oxygen species (ROS) levels as a result of pesticide usage and exposure can be associated with imbalances in cell homeostasis, which in turn, affects cellular components and DNA stability, and causes genotoxicity [42,[44][45][46][47][48]. A positive correlation between the incidence of various types of cancers such as leukemia, lung, and ovarian cancer as dependent variable and exposure to pesticides has been shown in many studies [13,29,30]. Besides the serious environmental and public health issues, different pest species have developed resistance to these chemicals, which leads to significant reduction in their effectiveness.…”
Section: Accepted Articlementioning
confidence: 99%